Ice Water Immersion as an Additional Method in Physiology Recovery in the Sport - Burboa Jair; Godoy Felipe; Soledad Riquelme María; Vivar Eugenia; Barahona Maximiliano; Zamorano Alvaro; Hinzpeter Jaime (International Physiology Journal, 2018)
Objective: Soccer has a reduced overall recovery time. If these situations are not properly controlled they can cause the athlete chronic fatigue, an increase in delayed-onset muscle soreness (DOMS) and thus result in a decrease in athletic performance. There are several therapies that have attempted to improve athletic performance, decrease the percentage of injuries and results in soccer. Training and recovery instances are opportunities to find ways to address this issue. Understanding the physiology of recovery is essential to accelerate some processes, with the aim of shortening the times. Subjects: Cryotherapy could improve functional performance tests and decrease pain in soccer players. Our work design is an experimental prospective study. Method: Twenty subjects (10 experimental subjects and 10 control group subjects), between the ages of 17 and 23, who are members of a university men's soccer team, participated in the study. The following variables were controlled: power; the number of jumps, the average height of a jump in a 30-second continuous jump test, and DOMS perception through visual analog scale (VAS). Both groups shall be subjected to a more active recovery as well as elongation carried out by the coaching staff. In addition to this, the experimental group shall also be subjected to ice baths (42-47 °F) for three minutes. Results: We found significant statistical differences in the number of jumps and the power of the same in the control group, thus obtaining improvements. No significant differences were observed in either group for the average jump height and percentage yield variables. In the assessment of DOMS significant differences were observed, with a lower perception of DOMS seen in the experimental group. Conclusion: Ice baths provide favorable results in some aspects of the 30-second continuous jump test, decreasing the perception of leg pain and fatigue, and therefore they can be considered a valid alternative in the management of these athletes.
Keywords: Sports performance